Does interbank market matter for business cycle fluctuation? An estimated DSGE model with financial frictions for the Euro area - Federico Giri (Kiel University, FinMaP - Financial Distortions and Macroeconomic Performance, 2014)
The aim of this paper is to assess the impact of the interbank market on the business cycle fluctuations. In order to do that, we build a DSGE model with heterogeneous households and banks. The surplus bank can allocate its resources between interbank lending and risk free government bonds. This portfolio choice is affected by an exogenous counterpart risk shock on the interbank lending. An increase of the counterpart risk diverts funds from the interbank markets toward the risk free market. This mechanism allow us to capture the collapse of the interbank market and the fly to quality mechanism underlying the 2007 financial crisis. The main result is that an interbank riskiness shock seems to explain part of the 2007 downturn and especially the rise of the interest rates on the credit market during and just after the financial turmoil.
info:eu-repo/grantAgreement/EC/FP7/612955
Keywords: E30; E44; E51; 330; DSGE model; financial frictions; interbank market; Bayesian estimation